Pengaruh Pemberian Tepung Biji Pepaya (Carica papaya) dengan Dosis Berbeda terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis niloticus) - Jakrin Daud; Arafik Lamadi; Rully Tuiyo (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to evaluate the effect of papaya (Carica papaya) seed flour at varying doses on the growth and survival of Nile tilapia (Oreochromis niloticus) seed. The study was conducted over 30 days at the Andalas Fish Seed Center (BBI), Kota Tengah, Gorontalo Province. The research used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The doses of papaya seed flour administered were P1 (control), P2 (150 g), P3 (200 g), and P4 (250 g). Observational parameters included weight growth, length growth, and survival rate. Data analysis was performed using statistical test; analysis of variance (ANOVA) to assess differences among treatments, followed by post-hoc tests for detailed comparison of each treatment. The findings indicate that the addition of papaya seed flour to the feed improved the weight growth rate of Nile tilapia, with the best result of 1.24% observed in treatment P3, while the best length growth of 1.06% was found in treatment P4, and the highest survival rate of 80% was achieved in treatment P3, compared to the lowest survival rate of 56% in treatment P1. However, the addition of papaya seed flour to the feed did not have a significant effect on length and weight growth but had a significant impact on survival rate. During the study, water quality parameters were recorded with temperatures ranging from 26-27°C, pH levels between 6.0-7.1 ppm, and dissolved oxygen (DO) levels between 5.3-5.5 mg/L.